Using an innovative flag element ratio approach to tracking potential sources of heavy metals on urban road surfaces. (December 2018) - Hong, Nian; Zhu, Panfeng; Liu, An; Zhao, Xu; Guan, Yuntao
Abstract: Heavy metals deposited on urban road surfaces can be washed-off by stormwater runoff, undermining stormwater reuse safety due to their high toxicity to ecological and human health. Heavy metals on urban road surfaces come from diverse sources and tracking these sources is essential to effectively manage stormwater and hence its reuse safety. This research study developed an innovative approach to tracking sources of heavy metals using data collected in Shenzhen, China. This approach developed was based on a "flag element ratio" theory, where each source generally corresponds to a specific ratio of targeted pollutants to the flag element. It is noted that Cr, Cu, Pb, Ni, and Zn on urban roads were 19.05 mg/kg to 152.01 mg/kg, 25.66 mg/kg to 310.75 mg/kg, 15.61 mg/kg to 220.35 mg/kg, 10.65 mg/kg to 100.28 mg/kg, and 138.14 mg/kg to 1047.05 mg/kg, respectively. Gasoline emission was the main source for Cr, Ni and Pb, while braking wear and tyre wear were the major sources of Cu and Zn, respectively. Furthermore, the rankings of sources of each heavy metal in terms of their contributions were obtained by using this approach. Vehicle exhaust was found as the main contributor for all the heavy metals on urban road surfaces. This highlighted that vehicle exhaust should be seriously considered in terms of controlling heavy metal pollution on urban road surfaces and hence resulting urban road stormwater runoff. Graphical abstract: Image 1 Highlights: We developed a novel approach to track source of heavy metals on urban road surfaces. The heavy metal concentrations on road surfaces ranged from 10.65 to 1047.05 mg/kg. Gasoline emission was the main source for Cr, Ni and Pb. Braking wear and tyre wear were the major sources of Cu and Zn, respectively. Ranking of heavy metal sources in terms of their contributions was obtained. Abstract : Development of a novel approach to tracking sources of heavy metals on urban road surfaces.